Resveratrol e suas implicações para a saúde - Brito, Fernanda Maranhão Lages de (2016)
Resveratrol consists of a phenolic compound accounting to the stilbene class, which has several biological properties. It is known to be widely distributed in nature and synthesized by various plants in response to infections and external stressors. Its main food sources are: grapes, red wine, peanuts and peanut butter. However, current knowledge of its pharmacokinetics, bioavailability and concentration in foodstuffs has led to increased consumption of this compound through dietary supplements, which have a high concentration and can be an alternative to increase its intake. The relationship between resveratrol and various pathological conditions occurred through the discovery of its possible mechanisms of action. Its properties as antioxidant, anti-inflammatory and analogical to caloric restriction have been discussed as its main effects on living beings. Animal studies have been extensively conducted and showed potential benefits of the use of resveratrol in the prevention and / or treatment of obesity, diabetes, cancer, cardiovascular disease, non-alcoholic fatty liver disease, among others. Faced with in vivo evidence, clinical trials started to be conducted to explore the benefits of this compound in the various pathologies to which it was originally associated. In order to contribute to the discussion of the problem, this dissertation presents two chapters: a literature review addressing various aspects of resveratrol, including structure, absorption, bioavailability, metabolism, and also highlighting the main findings about its relationship with various medical conditions; and a result article, which refers to a meta-analysis of randomized clinical trials, aimed to determine whether there are differences in the parameters of evaluation of non-alcoholic fatty liver disease in adult patients supplemented with resveratrol or placebo. To this end, searches were conducted in PUBMED, CENTRAL, SciELO, ClinicalTrials.gov and gray literature until May 2016. The primary outcome analyzed was the ALT and secondary outcomes were AST, GGT, TAG, total cholesterol, LDL- C, HDL-C, weight, glucose, insulin, and HOMA-IR. It was found 143 studies and, after evaluation, four were selected for quantitative analysis. No significant change was found for the outcomes analyzed, with the exception of glucose, which showed a significant reduction in individuals supplemented with resveratrol when compared to those supplemented with placebo (WMD -0.24 (95% CI -0.46 - -0.02) mmol / L, P = 0.03; I2= 27%, P=0.25). We conclude that, under the conditions of this study, resveratrol did not provide benefits as adjunctive treatment of NAFLD.